The discovery of the second specimen of Striartona clathrata (Poujade, 1886), hitherto known only from the female holotype (Lepidoptera: Zygaenidae, Procridinae, Artonini) - Huang, S.; Efetov, K. A. (SHILAP Revista de lepidopterología, 2021)
The second specimen of a rare and little known Procridinae species, Striartona clathrata (Poujade, 1886), was captured in Ningshan County, Shaanxi Province, Central China and is reported hereinafter. The adults and female genitalia of this specimen and the holotype of Striartona clathrata are compared and illustrated.